Endosymbiont Communities in Pachyseris speciosa Highlight Geographical and Methodological Variations - Jain, Sudhanshi S.; Afiq-Rosli, Lutfi; Feldman, Bar; Kunning, Ismael; Levy, Oren; Mana, Ralph R.; Wainwright, Benjamin J.; Huang, Danwei (Frontiers in Marine Science, 2021)
Reef-building corals live in symbiosis with the phototrophic dinoflagellate family Symbiodiniaceae, which comprises diverse genera such as Cladocopium and Durusdinium. Pachyseris speciosa, a widely distributed Indo-Pacific coral found in a variety of reef habitats, is known to be associated with these two Symbiodiniaceae genera, but little is known about the biogeographic variability of the endosymbiont communities across the region. In this study, the diversity and dominance patterns of Symbiodiniaceae at the western and eastern areas of the Central Indo-Pacific region were examined. We sampled Pachyseris speciosa colonies at seven and six sites in Singapore and Papua New Guinea, respectively, and genotyped their endosymbionts based on the internal transcribed spacer (ITS) markers using two distinct methods, quantitative polymerase chain reaction (qPCR) and high-throughput sequencing (HTS). Results showed 92% of all colonies in Singapore exhibiting Cladocopium dominance. There was a higher abundance of Durusdinium compared to Cladocopium in certain colonies from one site, Pulau Hantu (mean Durusdinium abundance of 90%, compared to 0–14% among all other sites). In contrast, variation in the endosymbiont communities was generally higher among sites in Papua New Guinea. Cladocopium expectedly dominated most colonies (75%), although colonies from Kimbe Bay (85%) and Kavieng (65%) showed Durusdinium dominance. Between localities, relative genus abundances based on qPCR were not significantly different, but HTS showed that the ratio of Durusdinium over Cladocopium was significantly higher in Papua New Guinea corals. Notably, 6% of colonies from Singapore and 15% from Papua New Guinea showed endosymbiont dominance patterns that were inconsistent between the two methods, underscoring the need for further validation of symbiotic algal quantification based on HTS. The richness of ITS2 type profiles was clearly lower among colonies from the impacted and turbid reefs of Singapore compared to the less urbanized reefs of Papua New Guinea. These coral intraspecific variations of Symbiodiniaceae communities within and among localities suggest that local conditions are important drivers of endosymbiosis and may ultimately influence corals’ resilience against global stressors such as ocean warming.